1998
DOI: 10.1002/(sici)1097-0274(199806)33:6<565::aid-ajim7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-related lung cancer mortality in Piedmont, Italy

Abstract: This study investigates the association between pleural neoplasm mortality, a possible proxy for asbestos exposure, and lung cancer mortality among males resident in Piedmont (northwestern Italy). Pleural neoplasm mortality was estimated in the 1,209 municipalities of the region for the period 1980–1992, applying Bayesian methods. The association with lung cancer mortality for municipalities was studied using Poisson regression. Urban/rural indicators and altitude were also included in the analysis. A positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In Italy, a study of LC mortality in an asbestos cementmanufacturing town (Casale Monferrato) reported an attributable risk among exposed of 67.5% for men and 51.3% for women, and among the general population (not occupationally exposed) of 18.3% for men and 10.1% for women (Magnani et al, 1997). An ecological study in Piedmont found that for a unit increase in the relative risk of pleural neoplasm, a 2.5% increase in LC mortality was estimated and 3.9% LC deaths were attributable to residence in municipalities with high pleural neoplasm mortality (proxy of asbestos exposure) (Martuzzi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a study of LC mortality in an asbestos cementmanufacturing town (Casale Monferrato) reported an attributable risk among exposed of 67.5% for men and 51.3% for women, and among the general population (not occupationally exposed) of 18.3% for men and 10.1% for women (Magnani et al, 1997). An ecological study in Piedmont found that for a unit increase in the relative risk of pleural neoplasm, a 2.5% increase in LC mortality was estimated and 3.9% LC deaths were attributable to residence in municipalities with high pleural neoplasm mortality (proxy of asbestos exposure) (Martuzzi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Its goal is to provide up-todate, clear information to both policy-makers and stakeholders to minimize human exposure to potentially harmful materials. When inhaled, asbestos fibers may give rise to either non-tumor diseases or malignant tumors in the lungs (Martuzzi et al 1999) and pleura (Mastrantonio et al 2002). Particular attention should be paid to the effects of asbestos on the rise of pleural mesothelioma (Bignon et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several questions remain open, but many epidemiological studies have demonstrated the importance of air pollution as a risk factor for mortality and morbidity [1][2][3][4][5][6][7][8][9]. For several specific health endpoints and pollutants, the associations have been quantified and concentration-response relationships have been characterised.…”
mentioning
confidence: 99%